Need a Good Book about Privacy? Evaluating Dictionary-Based Corpus Query for Detecting the Topic of Privacy in Literary Texts - Vogel, Carl; Edmond, Jennifer (My University, 2024)
This paper evaluates the usefulness of querying Vasalou et al.’s Privacy Dictionary (2011), a dictionary of 600+ words and phrases, in 131 canonical English-language novels from the long 19th century. We evaluate the word frequencies compared with a classification of the novels based on scholarly attention to the topic of privacy in each particular text. We report evidence of low- to low/medium strength of correlation between 3 of the 8 categories of the Privacy Dictionary and this classification. As a final step, by identifying the novels in our corpus which score highest in relative word frequency in these 3 categories, we suggest novels which have not yet received scholarly study on the topic of privacy but which may be promising for such studies. The highest scoring novel by our method, Maria Edgeworth’s Castle Rackrent (1800), seems indeed to be highly concerned with the topic of privacy, which is discussed in its author’s preface and opening pages.
PUBLISHED
Keywords: Digital Humanities; ARTIFICIAL INTELLIGENCE; Computational Linguistics; Digital Humanities; PRIVACY